Elastic Taping’s Effect on Exercise Capacity in Recreational Runner with Inspiratory Muscle Training - Asriningrum Asriningrum; Dewi Poerwandari; Andriati Andriati; Soenarnatalina Soenarnatalina (Surabaya Physical Medicine and Rehabilitation Journal, 2019)
Background: Running is a new trend of recreational sports in Indonesia. About 70% of recreational runners have difficulty in improving exercise capacity due to exercise-related transient abdominal pain (ETAP), caused by fatigue of the diaphragmatic muscles. Previous studies have shown that various training methods may increase diaphragmatic muscle strength and endurance, for example, inspiratory muscle training (IMT). Unfortunately, improvement of inspiratory muscle strength and endurance after exercise and IMT are still varies. Therefore, other methods are needed to optimize the effect of IMT. Application of the elastic taping on thoracic wall during exercise allows the inspiratory muscles to contract optimally which might improve functional capacity.Aim: To assess the effect of elastic taping on inspiratory muscle training using the pressure threshold IMT, in increasing the functional exercise capacity of recreational runners. Functional capacity was measured based on VO2max value, rating of perceived breathlessness (RPB) and rating of perceived exertion (RPE).Methods: an experimental study involved 14 nonsmoker recreational runners, ages 20-40 years, at Outpatient Clinic of Physical Medicine and Rehabilitation Department of Dr. Soetomo Hospital Surabaya. Subjects were divided into two groups (pressure threshold IMT with and without elastic taping groups), which were observed for four weeks. IMT was done five times a week, twice a day, with 30 repetitions, and 60% resistance 30 RM using Respironics®. Elastic taping Leukotape® was applied on the first until fifth day in each IMT sessions. The running exercises were done three times a week with EnMill® Treadmill ETB-03195 with a speed of 4.5 mph and 0% inclination. RBP, RPE and VO2max were measured using Borg Dyspneu scale, Borg Scale, and Bruce Treadmill Protocol test, respectively, before the first exercise and after 4 weeks of exercise.Results: There were an improvement of functional exercise capacity in both groups which were marked with a decline of RPB and RPE and increase of VO2max (p values < 0.05). However, there were no significant differences in the decrease of RPB and RPE and an increase of VO2max between groups (p values of were 0.31, 0.83, and 0.13, respectively). The effect of the elastic taping (r2 = 0.99) was not reflected in the differences of RPB, RPE and increasing VO2max.Conclusion: Inspiratory muscle training using pressure threshold IMT with or without the elastic taping for four weeks can improve exercise capacity of recreational runners.